Soil DOC release and aggregate disruption mediate rhizosphere priming effect on soil C decomposition. (May 2020) - He, Yanghui; Cheng, Weixin; Zhou, Lingyan; Shao, Junjiong; Liu, Huiying; Zhou, Huimin; Zhu, Kai; Zhou, Xuhui
Abstract: Roots and the associated rhizospheric activities regulate the mineralization of native soil organic matter (SOM), which is referred to as the rhizosphere priming effect (RPE). Although the importance of RPE for carbon cycle has increasingly been recognized, experimental evidence for how soil structural changes modulate the RPE is still unavailable. We addressed this issue by growing soybean plants (C3 ) in a C4 -derived soil in a continuous 13 C- labeling greenhouse. We hypothesized that root-induced soil structural change regulated the RPE by destabilizing soil matrix-protected organic carbon. Our results showed that the RPE was tightly coupled with plant photosynthetic activity, the disruption of coarse macro-aggregates, and the increased release of dissolved organic carbon (DOC) from the soil matrix. These findings indicate that living roots together with rhizodeposits not only can directly stimulate rhizospheric microbial activities, but also can make soil matrix-protected organic carbon available to microbial attacks and further enhance the RPE. This study suggests that the RPE on SOM mineralization is intimately linked with the dynamics of soil structures and DOC, which should be considered in future studies on mechanistic understanding and modeling of the RPE. Highlights: Belowground respiration was tightly coupled with aboveground photosynthesis. Soil structural changes modulated the rhizosphere priming effect. Rhizosphere processes stimulated DOC release originated from soil organic matter.